Impact of Anaemia and Dysregulated Iron Metabolism on COVID-19 Clinical Outcome – Review Article - Matea Bogović (Faculty of Medicine Osijek, 2021)
Coronavirus disease-19 (COVID-19) is a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that can manifest in a wide range of forms, but the most common symptoms are fever, headache, fatigue, respiratory problems, lost sense of smell and taste, sore throat, muscle pain and malaise.